The Relationship Between Sleep Disorders and Congenital Heart Disease in Children - Kaunang, Erling D; Salendu, Praevilia M; Wulur, Angelina F (National Journal of Community Medicine, 2025)
Background: Congenital heart disease (CHD) is the most common congenital anomaly in humans. Sleep quality in children with CHD may be compromised due to hypoxemia, cyanosis, and circulatory abnormalities. However, limited data are available, particularly in Indonesia. Objectives: This study aims to determine the relationship between sleep disorders and congenital heart disease in children. Methods: A cross-sectional study was conducted from November 2024 to March 2025 at Prof. Dr. R. D. Kandou General Hospital. Children aged 1 to <18 years with echocardiographically confirmed CHD were assessed using actigraphy and validated questionnaires. Sleep parameters included sleep efficiency, total sleep time, sleep latency, and wake after sleep onset (WASO). Bivariate and multivariate analyses were performed, with a significant value of p<0.05. Results: A total of 35 children with CHD were included (median age 3 years; 60% female). Sleep disturbances were highly prevalent, with 94% of children exhibiting at least one abnormal parameter. Multivariate analysis showed that female sex was independently associated with shorter total sleep time (β = –2.14 hours; 95% CI: –3.18 to –1.09; p < 0.001), and older age was associated with fewer total awakenings (β = –0.89; 95% CI: –1.50 to –0.28; p = 0.008). Conclusions: Sleep disorders are highly prevalent in children with CHD, particularly among females, malnourished children, and those with cyanotic defects. Targeted interventions are essential to improve sleep quality and overall health outcomes in this vulnerable population.